DISABILITY AS A CONSEQUENCE OF MENTAL DISORDERS: NEW METHODOLOGICAL APPROACHES FROM THE STANDPOINT OF THE INTERNATIONAL CLASSIFICATION OF FUNCTIONING - Borisova, I.S.; Ogorenko, V.V. (World of Medicine and Biology, 2024)
As of the beginning of 2017, about 300 thousand people with mental disorders in the country had a disability group, while the annual increase in persons with disabilities due to mental disorders is approximately 10 thousand people annually. It is important to develop methodological approaches to the classification of mental disorders from the standpoint of the social approach. The aim of the study was to determine the violations of vital activity criteria in persons with disabilities due to mental illness and their compliance with certain domains of the ICF to determine the feasibility of using this classifier in conducting medical and social expertise. The results showed a significant correlation between impairments of functions in the ICF domains and impairments of vital activity categories depending on the disability group. For the first time, new methodological approaches that combine medical criteria for disability and social approaches of the ICF are proposed. The application of this approach will improve the provision of expert assistance to the population from the standpoint of evidence-based medicine.
Keywords: disability and health; international classification of functioning; disability; mental disorders